Heart Failure and Disability in Community-Dwelling Older Adults in the United States—1999 to 2018: Data From National Health and Nutrition Examination Survey. (May 2022) - Seo, Yaewon; Wang, Jing; Barnes, Donelle; Barshikar, Surendra
To examine the associations of heart failure (HF) with five domains of disability while controlling for covariates. Subjects with HF and aged ≥ 50 years were selected from the 1999 to 2018 National Health and Nutrition Examination Survey data. Five domains of disability were measured with 19 physical tasks. Logistic regression with adjustment for covariates was conducted. The prevalence of HF in 27, 185 adults aged ≥ 50 years was 6.37%. After controlling for demographics and smoking, logistic regression showed that HF was associated with 2.8 to 3.4 times increased odds of all domains of disability compared to adults without HF, but with additional adjustments of covariates, the association was attenuated indicating the mediating effects of covariates. The future study may examine the mediating effects of covariates when intervening difficulties with lower extremity mobility and activities of daily living while considering in community-dwelling older adults with HF.